Development of bioactive films based on chitosan and Cynara cardunculus leaves extracts for wound dressings - Brás, Teresa (2021)
The development of natural based, effective and protective wound dressings associated to local treatment applied on chronic wounds, represents a major challenge nowadays. In this work chitosan-based films were prepared with different concentrations of ethanolic ultrasound assisted extracts from Cynara cardunculus leaves (EtPUAE). The physico-chemical film properties revealed that extract incorporation influences the volumetric swelling capacity and mechanical properties of the films, leading to materials with a lower fluid absorption capacity and more fragile. However, no impact was detected on the thermal properties of the films, as well as on their dense structure characterized by Scanning Electronic Microscopy (SEM) analysis. Biological screening of chitosan-based films show that chitosan with a 1% (w/w) and a 5% (w/w) EtPUAE loading did not induce cytotoxicity on normal human skin fibroblasts (Bj5-ta cell line), mainly attributed to cynaropicrin (extract key active compound) present in the film below its IC50 value. Nevertheless, chitosan-based films with 5% (w/w) EtPUAE presented an interesting anti-inflammatory activity. Bj5-ta cells stimulated with liposaccharides (LPS), presented a reduction of 86% on IL-6 cytokine levels, after exposure to chitosan with 5% EtPUAE film extract. The results obtained in this study open up the possibility of successfully using chitosan films doped with EtPUAE for development of chronic wound dressings, with the advantage of using naturally-sourced materials with anti-inflammatory activity